ANALISIS PENGARUH INTERMEDIASI DAN INKLUSI KEUANGAN TERHADAP STABILITAS SISTEM KEUANGAN DI INDONESIA - Fitrayansyah, Rudi; Fadli, Faishal (Contemporary Studies in Economic, Finance and Banking, 2024)
This study aims to determine how intermediation and financial inclusion affect financial system stability. Financial system stability is an important issue for the country's economy. In this case, financial inclusion and the role of intermediation have emerged as important components that can affect stability. The method used in this study is multiple linear regression method to see how third party funds, lending, number of accounts and number of ATMs affect financial system stability. Based on the findings in this study that intermediation consisting of third party fund variables has a significant negative effect on financial system stability  and credit variables have a significant positive effect on financial system stability as proxied by the financial system stability index, meaning that credit that is not accompanied by proper supervision and regulation will potentially cause instability in the financial system and financial inclusion consisting of variables number of accounts and number of ATMs has a significant negative effect on financial system stability as proxied by the financial system stability index.